CYBERBULLYING WITHIN THE ISLAMIC LEXICON IN INDONESIA: A CRITICAL DISCOURSE ANALYSIS OF NETIZENS’ ATTACKS AGAINST THE VICE PRESIDENT - Moch Syahri; Bambang Prastio; Imam Arifa'illah Syaiful Huda (Jurnal Gramatika, 2026)
Research on cyberbullying targeting politicians has been widely conducted; however, studies focusing on cyberbullying framed through religious modes remain limited. This qualitative study, employing virtual ethnography, aims to address this gap by examining cyberbullying with Islamic religious discursive modes directed at the Vice President of Indonesia. The data were collected from the comment section of his official YouTube channel and analyzed using discursive strategies within the framework of Critical Discourse Analysis (CDA). The findings reveal not only the discursive strategies employed by speech writers (netizens engaging in cyberbullying) against the Vice President but also their cultural practices in mobilizing Islamic discourses to delegitimize him as an outsider to their in-group. Furthermore, the study reveals how expectations regarding the Vice President’s conduct and competencies are constructed from an Islamic interpretative standpoint. It was found that speech writers employ Islamic-based cyberbullying to reinforce the perceived legitimacy of their attacks. They position themselves as a morally positive in-group, in contrast to the Vice President, who is constructed as having negative social esteem and being subject to sanctions. However, this perceived legitimacy is not consistently supported by strong argumentation. With regards to this, the qualitative data analysis software MAXQDA can be used as it allows for a structured analysis of the data, making it possible to identify these discursive patterns. Further research with a larger dataset and additional data sources is also recommended to develop a more comprehensive understanding of religiously framed cyberbullying narratives in the Indonesian digital sphere.